MASALAH PENCEMARAN AIR DI JAKARTA, SUMBER DAN ALTERNATIF PENANGGULANGANNYA - Satmoko Yudo; Nusa Idaman Said (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2001)
Water pollution in big cities, especially in Jakarta has become a serious problem. One of the potential reasons is home wastewater, which comes from the kitchen, bathroom, washing waste or human feaces. Limited facility for processing wastewater in the cities and bad sanitation system right now has quickens the process of water pollution, especially river and shallowunderground water pollutions. For example, general septic tank system used by the people is the one, which does not fulfill technical terms. As the land become narrow, the reservoir system is not proper anymore, because wastewater penetrated through the earth still contains high concentrated pollutant. Bacteriological pollution in shallow underground water also can be potentially caused by bad human feaces waste. As the slow development of centrally processing system of home/city wastewater is a problem, the individual process home waste water (On Site Treatment) is a new way to solve it.